Composite sodium ion battery positive electrode material with radial heterojunction and preparation method thereof
By constructing Ni0.3Mn0.7(OH)2 on the surface of Ni0.5Mn0.5(OH)2, a composite positive electrode material with radial anodic component distribution was synthesized, and the air stability and stability of the sodium ion battery positive electrode material was solved. The lack of cycle stability has achieved efficient improvement of materials and commercial application.
Patent Information
- Application Number
- CN202411472835.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing sodium ion battery positive electrode materials have shortcomings in air stability and cycling stability, which affects its battery performance.
By constructing Ni0.3Mn0.7(OH)2 of different thicknesses on the surface of Ni0.5Mn0.5(OH)2 precursor, a composite positive electrode material with radial anodic component distribution is synthesized to form a core-shell structure to enhance the air of the material Stability and cyclic stability.
It improves the air stability and cyclic stability of the cathode material of sodium ion battery, improves the kinetic performance of sodium ion transport, reduces material costs, and is suitable for commercial production.
Smart Images

Figure CN119050335B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a composite sodium ion battery positive electrode material with radial heterojunction and a preparation method thereof. Background Art
[0002] As society continues to progress, new energy vehicles are becoming more popular and developed, the demand for lithium resources is increasing rapidly. However, the limited reserves and uneven distribution of lithium resources have led to rising costs, limiting their application in large-scale power storage. In contrast, sodium-ion batteries have similar charging and discharging mechanisms to lithium-ion batteries, and sodium resources are abundant and widely distributed. Therefore, the development of sodium-ion battery technology has positive prospects for large-scale energy storage systems.
[0003] As a highly-regarded energy storage technology, the design and improvement of the positive electrode materials of sodium-ion batteries are crucial to improving battery performance. The key lies in improving the material's interfacial charge transfer, cycle structural stability, air stability and high-voltage stability. Summary of the invention
[0004] The purpose of the present invention is to provide a composite sodium ion battery positive electrode material with radial heterojunction and a preparation method thereof, which can reduce the material cost and adopt the method of preparing the composite sodium ion battery positive electrode material with radial heterojunction. 0.5 Mn 0.5 Ni with different thicknesses is constructed on the surface of (OH)2 precursor 0.3 Mn 0.7 (OH)2 method is used to synthesize a composite positive electrode material with radially heterogeneous component distribution, thereby improving the air stability and cycle stability of the material and the sodium ion transmission kinetics. The invention has low cost, simplicity and rationality, good electrical properties, and is suitable for commercial production.
[0005] To achieve the above-mentioned purpose, the present invention provides a composite sodium ion battery positive electrode material with a radial heterojunction. The positive electrode material is prepared by sintering a precursor and a sodium source. The prepared positive electrode material is a core-shell structure with a radial heterojunction. The core of the positive electrode material is an O3-type nickel-manganese-based layered oxide. There is a coating material on the surface of the core, and the coating material is a P2-type nickel-manganese-based layered oxide.
[0006] Preferably, the coating material has a thickness of 0-1 μm.
[0007] Preferably, the particle size of the precursor material is 3.6-4.2 μm, and the precursor is a core-shell structure, and the core chemical formula is Ni 0.5 Mn 0.5 (OH)2, Ni is deposited on the surface of the core 0.3 Mn 0.7 (OH)2,Ni 0.3 Mn 0.7The size of (OH)2 is x μm, where 0≤x≤1.
[0008] The present invention provides a method for preparing a composite sodium ion battery positive electrode material with a radial heterojunction, comprising the following steps:
[0009] Step 1, dissolving nickel salt and manganese salt in deionized water according to a proportion to obtain a mixed solution No. 1 and a mixed solution No. 2 respectively, adding a precipitant into deionized water to dissolve to prepare a precipitant solution, and diluting a complexing agent to a certain concentration to prepare a complexing agent solution;
[0010] Step 2: simultaneously introduce the No. 1 mixed solution, the precipitant solution and the complexing agent solution into a reactor protected by protective gas, maintain the pH and temperature in the reactor, take out the material when the reaction is carried out until the particle size of the material reaches the requirement, then switch the salt solution in the reactor from the No. 1 mixed solution to the No. 2 mixed solution, and repeat the above operation;
[0011] Step 3: Wash and dry the taken-out material to obtain Ni 0.5 Mn 0.5 (OH)2 and different sizes of Ni 0.3 Mn 0.7 (OH)2-coated precursor particles;
[0012] Step 4: uniformly mix the sodium source and the precursor particles according to a certain molar ratio to obtain a mixed material;
[0013] Step 5: Sinter the mixture in air atmosphere, then transfer it to an atmosphere furnace for further sintering, and finally synthesize a series of positive electrode materials Na x Ni y Mn z O2 samples.
[0014] Preferably, in step 1, the nickel salt is one or more of nickel sulfate, nickel nitrate and nickel chloride, the manganese salt is one or more of manganese sulfate, manganese nitrate and manganese chloride, the precipitant is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate and potassium bicarbonate, and the complexing agent is one or more of ammonia water and oxalic acid.
[0015] Preferably, the OH in the precipitant solution - / CO3 2- / HCO 3- The concentration is 3-7 mol / L, and the concentration of the complexing agent solution is 1.5-2 mol / L.
[0016] Preferably, the ratio of Ni to Mn in the No. 1 mixed solution is 1:1, the ratio of Ni to Mn in the No. 2 mixed solution is 3:7, and the concentrations of the No. 1 mixed solution and the No. 2 mixed solution are both 3-10 moL / L.
[0017] Preferably, the reactor has a capacity of 50 L, the protective gas is nitrogen or argon, the pH in the reactor is 11.0-11.6, and the ammonia concentration is maintained at 6-9 g / L.
[0018] Preferably, the sodium source in step 4 is one or more of Na2CO3, NaOH and NaNO3, and the sodium source and the precursor particles are evenly mixed in a molar ratio of Na:M=0.9:1.
[0019] Preferably, in step five, the mixed material is first sintered at 500° C. for 6 h in an air atmosphere, and then transferred to an atmosphere furnace in an oxygen atmosphere and sintered at 900° C. for 24 h.
[0020] Therefore, the present invention adopts the composite sodium ion battery positive electrode material with radial heterojunction and the preparation method, which has the following beneficial effects:
[0021] (1) Sodium-ion batteries have similar charging and discharging mechanisms as lithium-ion batteries. However, sodium resources are more abundant and widely distributed than lithium resources, making them less expensive. In addition, sodium-ion batteries are safer. They have relatively high internal resistance and generate less instantaneous heat in short-circuit conditions, making them safer and more resistant to cold and heat.
[0022] (2) The present invention achieves this by 0.5 Mn 0.5 (OH)2 surface construction of Ni with different thicknesses 0.3 Mn 0.7 (OH)2, and then synthesize a composite positive electrode material with radially heterogeneous component distribution, which solves the problems of poor air stability of O3-type nickel-manganese-based layered oxides, improves the air stability and cycle stability of the material, and improves the sodium ion transfer kinetics.
[0023] (3) The positive electrode material prepared by the present invention has good cycle performance and rate performance.
[0024] (4) The preparation method of the positive electrode material proposed in the present invention is simple to operate, low in cost, and has commercial application value.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of a precursor prepared in Example 2 of a composite sodium ion battery positive electrode material with radial heterojunction and a preparation method of the present invention;
[0027] Figure 2 This is a SEM image of the positive electrode material prepared in Example 2 of the composite sodium ion battery positive electrode material with radial heterojunction and preparation method of the present invention;
[0028] Figure 3 This is a partial enlarged SEM image of a precursor prepared in Example 2 of the composite sodium ion battery positive electrode material with radial heterojunction and preparation method of the present invention;
[0029] Figure 4 This is a partial enlarged SEM image of the positive electrode material prepared in Example 2 of the composite sodium ion battery positive electrode material with radial heterojunction and preparation method of the present invention;
[0030] Figure 5 This is the XRD diagram of the positive electrode material prepared in Example 2 of the composite sodium ion battery positive electrode material and preparation method having radial heterojunction of the present invention;
[0031] Figure 6 This is a comparison chart of the cycle performance of Example 2 of the composite sodium ion battery positive electrode material with radial heterojunction and preparation method of the present invention and Comparative Example 1 at 2.0-4.0V. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0034] Example
[0035] The present invention provides a composite sodium ion battery positive electrode material with a radial heterojunction. The positive electrode material is prepared by sintering a precursor and a sodium source. The prepared positive electrode material is a core-shell structure with a radial heterojunction. The inner core of the positive electrode material is an O3-type nickel-manganese-based layered oxide. There is a coating material on the surface of the inner core. The coating material is a P2-type nickel-manganese-based layered oxide. The thickness of the coating material is 0-1 μm.
[0036] The particle size of the precursor material is 3.6-4.2 μm, and the precursor is a core-shell structure, and the core chemical formula is Ni 0.5 Mn 0.5 (OH)2, Ni is deposited on the surface of the core 0.3 Mn 0.7 (OH)2,Ni 0.3 Mn 0.7 The size of (OH)2 is x μm, where 0≤x≤1.
[0037] The present invention also provides a method for preparing a composite sodium ion battery positive electrode material having a radial heterojunction, comprising the following steps:
[0038] Step 1: Dissolve nickel salt and manganese salt in deionized water in proportion to obtain mixed solution No. 1 and mixed solution No. 2 respectively, add precipitant to deionized water to dissolve to prepare precipitant solution, and dilute the complexing agent to a certain concentration to prepare complexing agent solution; nickel salt (such as nickel sulfate, nickel chloride, etc.) can increase the nickel content in the positive electrode material, thereby improving the energy density of the battery. The increase in the proportion of nickel can enable the battery to store more electrical energy and increase endurance. The addition of manganese salts (such as manganese sulfate, manganese nitrate, etc.) can improve the structural stability and safety of the positive electrode material. Manganese helps to form a stable lattice structure, resisting structural changes caused during the charge and discharge cycle, thereby extending the battery life.
[0039] The ratio of Ni to Mn in the No. 1 mixed solution is 1:1, and the concentration of each solution is 2M. The ratio of Ni to Mn in the No. 2 mixed solution is 3:7, and the concentration of each solution is 2M. The concentrations of the obtained No. 1 mixed solution and No. 2 mixed solution are both 3-10moL / L. By adjusting the ratio of nickel and manganese, the charge and discharge efficiency, cycle stability and rate performance of the battery can be optimized to meet the needs of different application fields.
[0040] The nickel salt is one or more of nickel sulfate, nickel nitrate and nickel chloride, the nickel sulfate is nickel sulfate hexahydrate, the manganese salt is one or more of manganese sulfate, manganese nitrate and manganese chloride, and the manganese sulfate is manganese sulfate monohydrate. The precipitant is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate and potassium bicarbonate, and the complexing agent is one or more of ammonia water and oxalic acid.
[0041] OH in the precipitant solution - / CO3 2- / HCO 3- The concentration is 3-7 mol / L, and the concentration of the complexing agent solution is 1.5-2 mol / L. The complexing agent can form a stable complex with metal ions and can also increase the solubility of metal salts. The precipitant can promote the pre-reaction of metal ions in the solution to form a precipitate that is insoluble in water.
[0042] Step 2: Introduce mixed solution No. 1, precipitant solution and complexing agent solution into a reactor protected by protective gas at the same time, maintain the pH and temperature in the reactor, take out the material when the reaction is carried out until the particle size of the material reaches the requirement, then switch the salt solution in the reactor from mixed solution No. 1 to mixed solution No. 2, and repeat the above operation.
[0043] Step 3: Wash and dry the taken-out material to obtain precursor particles of different sizes. The precursor particles are Ni 0.5 Mn 0.5 (OH)2 and different sizes of Ni 0.3 Mn 0.7(OH)2-coated particles. During the reaction of the first mixed solution, the material was taken out when the particle size reached 3.6 μm; during the reaction of the second mixed solution, the material was taken out when the particle size reached 3.8, 4.0 and 4.2 μm respectively.
[0044] Step 4: Evenly mix the sodium source and the precursor particles in a certain molar ratio to obtain a mixed material; the sodium source is one or more of Na2CO3, NaOH and NaNO3, and the sodium source and the precursor particles are evenly mixed in a molar ratio of Na:M=0.9:1.
[0045] Step 5: Sinter the mixture in air atmosphere, then transfer it to an atmosphere furnace for further sintering, and finally synthesize a series of positive electrode materials Na x Ni y Mn z O2 sample, in which the mixed material was first sintered at 500°C in an air atmosphere for 6 h, and then transferred to an atmosphere furnace with an oxygen atmosphere and sintered at 900°C for 24 h. The finally synthesized positive electrode materials were recorded as NM, NM+0.2μm, NM+0.4μm and NM+0.6μm, respectively.
[0046] Example 1
[0047] This embodiment prepares a composite sodium ion battery positive electrode material with a radial heterojunction, comprising the following steps:
[0048] (1) Nickel sulfate hexahydrate and manganese sulfate monohydrate were dissolved in deionized water in the required ratio to obtain two mixed solutions. The Ni:Mn ratio in mixed solution No. 1 was 1:1, and the Ni:Mn ratio in mixed solution No. 2 was 3:7, and the concentration of both solutions was 2M.
[0049] (2) First, the mixed solution No. 1, 4M NaOH solution and 2M NH3·H2O solution were simultaneously introduced into a reactor with nitrogen as the protective gas, the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 3.6 μm, 200 g of the material was taken out.
[0050] Then, the No. 1 mixed solution was switched to the No. 2 mixed solution, the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 3.8 μm, 200 g of the material was taken out each time; the precursor particles were screened out after washing and drying, wherein the core of the precursor particles was Ni 0.5 Mn 0.5 (OH)2, with Ni deposited on the surface of the core with a size of 0.2 μm 0.3 Mn 0.7 (OH)2.
[0051] (3) Na2CO3 and precursor particles were mixed evenly at a molar ratio of 0.9:1 (Na:M) to obtain a mixed material, which was first sintered at 500°C for 6 h in an air atmosphere, and then transferred to an atmosphere furnace in an oxygen atmosphere and sintered at 900°C for 24 h. The positive electrode material sample was obtained and marked as NM+0.2μm.
[0052] (4) Measure the first cycle discharge specific capacity and capacity retention rate after 300 cycles of the composite sodium ion battery positive electrode material with radial heterojunction.
[0053] Example 2
[0054] This embodiment prepares a composite sodium ion battery positive electrode material with a radial heterojunction, comprising the following steps:
[0055] (1) Nickel sulfate hexahydrate and manganese sulfate monohydrate were dissolved in deionized water in the required ratio to obtain two mixed solutions. The Ni:Mn ratio in mixed solution No. 1 was 1:1, and the Ni:Mn ratio in mixed solution No. 2 was 3:7, and the concentration of both solutions was 2M.
[0056] (2) First, the mixed solution No. 1, 4M NaOH solution and 2M NH3·H2O solution were simultaneously introduced into a reactor with nitrogen as the protective gas, the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 3.6 μm, 200 g of the material was taken out.
[0057] Then, the No. 1 mixed solution was switched to the No. 2 mixed solution, the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 4.0 μm, 200 g of the material was taken out each time; the precursor particles were screened out after washing and drying, wherein the core of the precursor particles was Ni 0.5 Mn 0.5 (OH)2, with Ni deposited on the surface of the core with a size of 0.4 μm 0.3 Mn 0.7 (OH)2.
[0058] (3) Na2CO3 and precursor particles are uniformly mixed in a molar ratio of 0.9:1 (Na:M) to obtain a mixed material. The mixed material is first sintered at 500°C for 6 h in an air atmosphere, and then transferred to an atmosphere furnace with an oxygen atmosphere and sintered at 900°C for 24 h to obtain the positive electrode material sample, which is marked as NM+0.4 μm.
[0059] (4) Measure the first cycle discharge specific capacity and cycle retention rate after 300 cycles of the composite sodium ion battery positive electrode material with radial heterojunction.
[0060] Figure 1 The SEM image of the prepared precursor is shown in Figure 2. Figure 3 This is a partial enlarged SEM image of the prepared precursor. It can be seen from the image that the precursor particles were successfully prepared, and the prepared precursor has good particle morphology and distribution. Figure 2 This is the SEM image of the prepared positive electrode material. Figure 4 This is a partial enlarged SEM image of the prepared positive electrode material. Figure 5 is the XRD pattern of the prepared positive electrode material. Figure 2 , Figure 4 and Figure 5 It can be seen that the positive electrode material has been successfully prepared, and the prepared precursor particles and the positive electrode material both have a two-phase structure.
[0061] Example 3
[0062] This embodiment prepares a composite sodium ion battery positive electrode material with a radial heterojunction, comprising the following steps:
[0063] (1) Nickel sulfate hexahydrate and manganese sulfate monohydrate were dissolved in deionized water in the required ratio to obtain two mixed solutions. The Ni:Mn ratio in mixed solution No. 1 was 1:1, and the Ni:Mn ratio in mixed solution No. 2 was 3:7, and the concentration of both solutions was 2M.
[0064] (2) First, the mixed solution No. 1, 4M NaOH solution and 2M NH3·H2O solution were simultaneously introduced into a reactor with nitrogen as the protective gas, the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 3.6 μm, 200 g of the material was taken out.
[0065] Then, the No. 1 mixed solution was switched to the No. 2 mixed solution, the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 4.2 μm, 200 g of the material was taken out each time; the precursor particles were screened out after washing and drying, and the core of the precursor particles was Ni 0.5 Mn 0.5 (OH)2, with Ni deposited on the surface of the core with a size of 0.6 μm 0.3 Mn 0.7 (OH)2.
[0066] (3) Na2CO3 and precursor particles were mixed evenly at a molar ratio of 0.9:1 (Na:M) to obtain a mixed material, which was first sintered at 500°C for 6 h in an air atmosphere, and then transferred to an atmosphere furnace in an oxygen atmosphere and sintered at 900°C for 24 h. The positive electrode material sample was obtained and marked as NM+0.6μm.
[0067] (4) Measure the first cycle discharge specific capacity and capacity retention rate after 300 cycles of the composite sodium ion battery positive electrode material with radial heterojunction.
[0068] Comparative Example 1
[0069] The preparation of the positive electrode material for sodium ion batteries comprises the following steps:
[0070] (1) Nickel sulfate hexahydrate and manganese sulfate monohydrate were dissolved in deionized water in the required ratio to obtain two mixed solutions. The Ni:Mn ratio in mixed solution No. 1 was 1:1, and the Ni:Mn ratio in mixed solution No. 2 was 3:7, and the concentration of both solutions was 2M.
[0071] (2) First, the No. 1 mixed solution, 4M NaOH solution, and 2M NH3·H2O solution were simultaneously introduced into a reactor with nitrogen as the protective gas, and the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L. When the particle size of the material in the reactor reached 3.6 μm, 200 g of the material was taken out; then the No. 1 mixed solution was switched to the No. 2 mixed solution, and the pH in the reactor was maintained at 11.2, and the ammonia concentration was maintained at 7.5 g / L; after washing and drying, the positive electrode material Ni 0.5 Mn 0.5 (OH)2, marked as NM.
[0072] (3) Measure the first-cycle discharge specific capacity and capacity retention rate after 300 cycles of the composite sodium-ion battery positive electrode material with radial heterojunction.
[0073] The composite sodium ion battery positive electrode material with radial heterojunction obtained in Examples 1-3 and the NM material obtained in Comparative Example 1 were used as positive electrodes, and metal lithium sheets were used as negative electrodes. They were assembled into button batteries for charge and discharge comparison tests. The test results are shown in the following table:
[0074] Table 1 Discharge capacity test data of battery positive electrode materials
[0075] ;
[0076] It can be concluded from Table 1 that the composite sodium ion battery positive electrode material with radial heterojunction obtained in Examples 1-3 is used as the positive electrode, and the metal lithium sheet is used as the negative electrode to assemble a button battery for charge and discharge comparison test. The first-cycle discharge capacity can reach up to 119.61 mAh / g at a rate of 1C, and the capacity retention rate after 300 cycles can reach up to 64.61. Although the first-cycle discharge capacity of the NM material obtained in Comparative Example 1 as the positive electrode reaches 134.82 mAh / g, the capacity retention rate after 300 cycles is only 11.69%.
[0077] It can be seen that the cycle stability of the battery made of the composite sodium-ion battery positive electrode material with radial heterojunction is much higher than that of the battery made of the ordinary sodium-ion battery positive electrode material. On the whole, the battery made of the composite sodium-ion battery positive electrode material with radial heterojunction is better than the battery made of the ordinary sodium-ion battery positive electrode material, and the optimal thickness of the coating material of the composite sodium-ion battery positive electrode material with radial heterojunction is 0.4μm.
[0078] Figure 6 This is a comparison chart of the cycle performance of Example 2 and Comparative Example 1 at 2.0-4.0V. It can be seen from the figure that Example 2 performs well under long cycle conditions and can maintain a higher specific energy.
[0079] Therefore, the present invention adopts the composite sodium ion battery positive electrode material with radial heterojunction and the preparation method, while reducing the material cost, using Ni 0.5 Mn 0.5 Ni with different thicknesses is constructed on the surface of (OH)2 precursor 0.3 Mn 0.7 (OH)2 method is used to synthesize a composite positive electrode material with radially heterogeneous component distribution, thereby improving the air stability and cycle stability of the material and the sodium ion transmission kinetics. The invention has low cost, simplicity and rationality, good electrical properties, and is suitable for commercial production.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite sodium ion battery positive electrode material with a radial heterojunction, characterized in that: The positive electrode material is prepared by sintering a precursor and a sodium source. The prepared positive electrode material is a core-shell structure with a radial heterojunction. The core of the positive electrode material is an O3-type nickel-manganese-based layered oxide. There is a coating material on the surface of the core. The coating material is a P2-type nickel-manganese-based layered oxide. The thickness of the coating material is less than 1 μm. The precursor is a core-shell structure, and the core chemical formula is Ni 0.5 Mn 0.5 (OH)2, Ni is deposited on the surface of the core 0.3 Mn 0.7 (OH)2; The method for preparing the above-mentioned positive electrode material comprises the following steps: Step 1, dissolving nickel salt and manganese salt in deionized water according to a proportion to obtain a mixed solution No. 1 and a mixed solution No. 2 respectively, adding a precipitant into deionized water to dissolve to prepare a precipitant solution, and diluting a complexing agent to a certain concentration to prepare a complexing agent solution; Step 2: simultaneously introduce the No. 1 mixed solution, the precipitant solution and the complexing agent solution into a reactor protected by protective gas, maintain the pH and temperature in the reactor, take out the material when the reaction is carried out until the material particle size reaches the requirement, then switch the salt solution in the reactor from the No. 1 mixed solution to the No. 2 mixed solution, repeat the above operation, and keep the ammonia concentration at 7.5 g / L; Step 3: Wash and dry the taken out material to obtain Ni of corresponding size. 0.3 Mn 0.7 (OH)2 coated Ni 0.5 Mn 0.5 (OH)2 precursor particles, Ni 0.3 Mn 0.7 (OH)2 size is x μm, where 0 <x≤1; Step 4: uniformly mix the sodium source and the precursor particles according to a certain molar ratio to obtain a mixed material, wherein the sodium source and the precursor particles are uniformly mixed according to a molar ratio of Na:M=0.9:1; Step 5: Sinter the mixture in air atmosphere, then transfer it to an atmosphere furnace for further sintering, and finally synthesize a series of positive electrode materials Na x Ni y Mn z O2 sample; the mixed material was first sintered at 500°C in an air atmosphere for 6 h, and then transferred to an atmosphere furnace with an oxygen atmosphere and sintered at 900°C for 24 h.
2. The method for preparing a composite sodium ion battery positive electrode material with a radial heterojunction according to claim 1, characterized in that: The particle size of the precursor material is 3.6-4.2 μm.
3. The method for preparing a composite sodium ion battery positive electrode material with radial heterojunction according to claim 1, characterized in that: In the step 1, the nickel salt is one or more of nickel sulfate, nickel nitrate and nickel chloride, the manganese salt is one or more of manganese sulfate, manganese nitrate and manganese chloride, the precipitant is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate and potassium bicarbonate, and the complexing agent is one or more of ammonia water and oxalic acid.
4. The method for preparing a composite sodium ion battery positive electrode material with radial heterojunction according to claim 1, characterized in that: The precipitant solution contains OH - / CO3 2- / HCO 3- The concentration is 3-7 mol / L, and the concentration of the complexing agent solution is 1.5-2 mol / L.
5. The method for preparing a composite sodium ion battery positive electrode material with radial heterojunction according to claim 1, characterized in that: The ratio of Ni to Mn in the No. 1 mixed solution is 1:1, the ratio of Ni to Mn in the No. 2 mixed solution is 3:7, and the concentrations of the No. 1 mixed solution and the No. 2 mixed solution are both 3-10 moL / L.
6. The method for preparing a composite sodium ion battery positive electrode material with radial heterojunction according to claim 1, characterized in that: The reactor has a capacity of 50 L, the protective gas is nitrogen or argon, and the pH in the reactor is 11.0-11.
6.
7. The method for preparing a composite sodium ion battery positive electrode material with radial heterojunction according to claim 1, characterized in that: The sodium source in step 4 is one or more of Na2CO3, NaOH or NaNO3.
Citation Information
Patent Citations
Positive electrode material precursor, positive electrode material, preparation method of positive electrode material and sodium ion battery
CN114920306A
Preparation method of precursor, precursor and positive electrode material
CN115745026A